23/4x=67/8

Simple and best practice solution for 23/4x=67/8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23/4x=67/8 equation:


x in (-oo:+oo)

(23/4)*x = 67/8 // - 67/8

(23/4)*x-(67/8) = 0

(23/4)*x-67/8 = 0

23/4*x-67/8 = 0 // + 67/8

23/4*x = 67/8 // : 23/4

x = 67/8/23/4

x = 67/46

x = 67/46

See similar equations:

| -4(5t-3)+8t=7t-2 | | (4x-6)=3(4x-3) | | x+6/5+x+3/x=3 | | 7y+5=-6y-21 | | 2z+2=2-2z | | 6x+20=4x-36 | | 4r+7=-43 | | n^2+n=2n | | 7h-10=-4 | | -1-7x-6(-7-x)=36 | | (2a+4b)(3a-b)=0 | | 7h-10=4 | | (7a-7)(6a-4)= | | (7a-7)(6a-4)= | | 4p+7p^2= | | 3g+14=-7 | | (-90)+(-56)= | | 7x-8y=21+40 | | 3g+14=7 | | 1-sqrt(2x-4)=sqrt(5-x) | | 4y+4y+13=90 | | 3(2x^2+3)=4(2x+3) | | 2d-5=-13 | | 5x+20=7x+2 | | 2r+3s=1 | | 3x+1x-7= | | 31=-11x+3-x^2 | | 3/4x+6=-9 | | (-10)(-2)= | | 1/8(6t-8)=t+8/16 | | 5(3-w)+3=-3(w-4)-8 | | 1+qwertyuiop=9 |

Equations solver categories